2020
DOI: 10.3389/fonc.2020.571601
|View full text |Cite
|
Sign up to set email alerts
|

MKI-1, a Novel Small-Molecule Inhibitor of MASTL, Exerts Antitumor and Radiosensitizer Activities Through PP2A Activation in Breast Cancer

Abstract: Although MASTL (microtubule-associated serine/threonine kinase-like) is an attractive target for anticancer treatment, MASTL inhibitors with antitumor activity have not yet been reported. In this study, we have presented a novel MASTL inhibitor, MKI-1, identified through in silico screening and in vitro analysis. Our data revealed that MKI-1 exerted antitumor and radiosensitizer activities in in vitro and in vivo models of breast cancer. The mechanism of action of MKI-1 occurred through an increase in PP2A act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…PP2A hyperphosphorylation, as well as upregulation of the endogenous PP2A inhibitors such as SET, has been reported as main molecular mechanisms of PP2A inhibition in many tumors including breast cancer. These alterations have progressively emerged as promising therapeutic targets in this disease [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Although it has been recently reported that PP2A inhibition is a frequent alteration in breast cancer related with poor outcome and therapy resistance, such studies have been carried out in cohorts including cases with different molecular subtypes [ 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…PP2A hyperphosphorylation, as well as upregulation of the endogenous PP2A inhibitors such as SET, has been reported as main molecular mechanisms of PP2A inhibition in many tumors including breast cancer. These alterations have progressively emerged as promising therapeutic targets in this disease [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Although it has been recently reported that PP2A inhibition is a frequent alteration in breast cancer related with poor outcome and therapy resistance, such studies have been carried out in cohorts including cases with different molecular subtypes [ 40 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MASTL are highly expressed in multiple types of cancers, including breast, head and neck, gastric, thyroid, and colorectal cancers [ 12 , 15 , 17 , 18 , 19 , 20 ]. MASTL inhibition selectively eradicated proliferative cancer cells rather than normal cells by inducing mitotic catastrophe [ 12 , 21 , 22 ]. Therefore, accumulating evidence clearly indicates that MASTL is an attractive, druggable target for selective anticancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several groups reported candidate compounds as potential MASTL inhibitors [ 22 , 23 , 24 ]. Greatwall kinase inhibitor-1 (GKI-1) was reported as a first-line inhibitor against MASTL, which was designed by using the solved protein structure of the kinase domain of MASTL [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations